Differences In Income Of Group And Non-Group Farmers In Lainea District, South Konawe District - Asma Jayanti; Ilma Sarimustaqiyma Rianse; Hidrawati Hidrawati (Cita konsultindo, 2023)
This research aims to determine the difference in income between grouped and non-grouped farmers. Research data collection took place from May to July 2022. The population in this study was 161 people, the sample was determined using the Slovin formula, where 61 farmers were grouped and 28 farmers were not grouped. The data in the research are primary data and secondary data using observation and interview techniques. The research results show that the role of farmer groups is very important in increasing group income, the total income of group farmers is IDR 658,064,499; with an average value of IDR 10,787,943; and the income of non-group farmers is IDR 243,538,000; with an average of IDR 8,679,786.